3f(-3)+h(5)=

Simple and best practice solution for 3f(-3)+h(5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3f(-3)+h(5)= equation:


Simplifying
3f(-3) + h(5) = 0

Reorder the terms for easier multiplication:
3 * -3f + h(5) = 0

Multiply 3 * -3
-9f + h(5) = 0

Reorder the terms for easier multiplication:
-9f + 5h = 0

Solving
-9f + 5h = 0

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-5h' to each side of the equation.
-9f + 5h + -5h = 0 + -5h

Combine like terms: 5h + -5h = 0
-9f + 0 = 0 + -5h
-9f = 0 + -5h
Remove the zero:
-9f = -5h

Divide each side by '-9'.
f = 0.5555555556h

Simplifying
f = 0.5555555556h

See similar equations:

| 9+-5x=4 | | -19+x=-19 | | -7(k-8)-(-8k+6)=-2 | | 20z-5-12x=10z+8 | | 1.5/6=3/x | | 0.85(x)=200 | | -7(k-8)-(-k+6)=-2 | | N*1/5=9 | | 10(2+x)=15(x+1)+15 | | -3*x+9-2x=-12-5x | | g^2+16g+59=0 | | 5(3x-2)-3(x-1)=1000 | | 4x+4-7x-2=3x-6x-11 | | 15+7+17y=2y+70 | | X*y*.75=48 | | X^2-8x+10=58 | | -10+7x-10=1 | | -17y(y-2)=-17y+64 | | -4=7+x+6x | | 20x-3=11x-1 | | 8(p-3)=24p | | 8(y-3)=24p | | 8(x-3)+2(4x-6)=9x-15 | | 9-10n=-111 | | 2y+12=5y-8 | | 13p=182 | | 2(t-2)+5t=6t-41 | | 13p=180 | | 244x=7/8 | | m^2=-3 | | 4y^2=6-5y | | 224-7/8 |

Equations solver categories